1995
DOI: 10.1083/jcb.130.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin II induces endothelial cell capillary tube formation.

Abstract: We studied the formation of capillary tubes by endothelial cells which were sandwiched between two fibrin gels under serum-free conditions. After formation of the overlying fibrin gel, the endothelial cell monolayer rearranged into an extensive net of capillary tubes. Tube formation was apparent at 5 h and was fully developed by 24 h. The capillary tubes were vacuolated, and both intracellular and intercellular lumina were present. Maximal tube formation was observed with fibrin II (which lacks both fibrinopep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 45 publications
6
125
0
1
Order By: Relevance
“…We have shown that lung, prostate and breast cancer epithelial cells synthesize and secrete Fg that enhances FGF-2-mediated cell proliferation, assembles into extracellular matrices and binds to cancer cell surfaces. 2,14,[32][33][34][35][36][37] In addition, others have demonstrated Fg production in adenocarcinoma cell lines of cervical 15 and intestinal 16 origin. Recent expression array profiling studies have confirmed that the Fg genes are expressed in breast 17 and lung carcinomas 18,19 isolated from patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that lung, prostate and breast cancer epithelial cells synthesize and secrete Fg that enhances FGF-2-mediated cell proliferation, assembles into extracellular matrices and binds to cancer cell surfaces. 2,14,[32][33][34][35][36][37] In addition, others have demonstrated Fg production in adenocarcinoma cell lines of cervical 15 and intestinal 16 origin. Recent expression array profiling studies have confirmed that the Fg genes are expressed in breast 17 and lung carcinomas 18,19 isolated from patients.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control peptide corresponding to fibrinopeptide A induced minimal %FITC-Dextran Flux compared with Fg or peptide b 15-42 (#p < 0.0001); however, the 13% relative fluorescence was significant (-p 5 0.001) compared with basal levels that were 1% of intact Fg-induced permeability. Peptides missing b 15-17 residues (b [18][19][20][21][22][23][24][25][26][27][28][29][30][31] or b [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] ) or truncated at the C-terminus (b [15][16][17][18][19][20][21][22][23][24][25][26][27] (Fig. 2c).…”
Section: Fg-induced Ec Permeability Involves Fg-b 15-42 Sequences Andmentioning
confidence: 99%
See 3 more Smart Citations